Inovasi Pembelajaran Berbasis Karakter di Era Industri 4.0 - Rahmat Joko Nugroho (LPPM IAINU Kebumen, 2019)
Learning innovation is an ongoing teaching and learning process present something new so as to eliminate boredom and bored. Innovative learning always brings something new in every class educational elements ranging from aspects of teacher strategy, materials and tools several other important elements. The learning process in schools, universities is the essence of education at all levels that needs to be improved in quality.In the learning process, students must gain learning experience to solve the problems encountered. Innovative learning is learning that is more student centered. That is, more learning provide opportunities for students / students to construct knowledge independently (self-directed) and mediated by peers (peer-mediated instructions). Innovative learning bases itself on a constructivist paradigm. Character education is currently receiving such attention important in the education system in Indonesia. This is in accordance with the law Number 20 of 2003 concerning the National Education System article 3, which states that national education functions to develop capabilities and form dignified national character and civilization in order to educate nation's life. National education belongs to the development of potential students to become human beings who believe and fear God Almighty, having noble character, being healthy, knowledgeable, capable, creative, independent and being a citizen democratic and responsible state. This writing has the objectives: (1) to explain about learning to explain instilling character values ​​through contextual learning innovations, (2)explains the concept of planting character education through learning innovation quantum (3) explains instilling character values ​​through innovation competency-based learning (4) explains the concept of learning in the era industry 4.0